Spontaneous pneumothorax in children in the South-east of Turkey - Eren, S; Gurkan, F; Balci, AE; Ulku, R; Onat, S; Eren, MN (Wiley, 2004)
Background: The purpose of the present study was to investigate the etiological factors, symptomatology, management and outcome of spontaneous pneumothorax in children aged <15 years. Methods: The authors' reviewed the records of 44 children with spontaneous pneumothorax between January 1990 and February 2002. Results: The median age was 4.6 years (range 2 months-14 years), and 51% were male. Breathlessness and coughing were the most common symptoms. All pneumothoraces were initially managed by closed tube drainage. Thirty-seven (84%) of the children responded well and were cured of pneumothorax with closed tube thoracostomy alone. Seven children (16%) underwent thoracotomy. The median hospital stay was 12.9 days. There were two deaths from respiratory failure. Six- to 96-month follow-up information was available for 32 patients, and only one recurrence was found. Conclusions: Lung infections were the most frequently observed underlying pathology in the patients studied. Closed tube thoracostomy alone was sufficient for the majority of patients.
Keywords: children; spontaneous pneumothorax